The status of private military companies under international humanitarian law; towards a new convention - Daniels, Caroline (Department of Public Law, 2014)
The public-private dichotomy of warfare is crumbling down as governments are voluntarily surrendering one of the essential and defining attributes of statehood: the state's monopoly on the legitimate use of force, leading to the privatization of war and conflicts